Advances in Inkjet‐Printed Metal Halide Perovskite Photovoltaic and Optoelectronic Devices. Issue 4 (3rd December 2019) - Mathies, Florian; List-Kratochvil, Emil J. W.; Unger, Eva L.
Abstract : Inkjet printing (IJP) has evolved over the past 30 years into a reliable, versatile, and cost‐effective industrial production technology in many areas from graphics to printed electronic applications. Intensive research efforts have led to the successful development of functional electronic inks to realize printed circuit boards, sensors, lighting, actuators, energy storage, and power generation devices. Recently, a promising solution‐processable material class has entered the stage: metal halide perovskites (MHPs). Within just 10 years of research, the efficiency of perovskite solar cells (PSCs) on a laboratory scale increased to over 25%. Despite the complex nature of MHPs, significant progress has also been made in controlling film formation in terms of ink development, substrate wetting behavior, and crystallization processes of inkjet‐printed MHPs. This results in highly efficient inkjet‐printed PSCs with a power conversion efficiency (PCE) of almost 21%, paving the way for cost‐effective and highly efficient thin‐film solar cell technology. In addition, the excellent optoelectronic properties of inkjet‐printed MHPs achieve remarkable results in photodetectors, X‐ray detectors, and illumination applications. Herein, a comprehensive overview of the state‐of‐the‐art and recent advances in the production of inkjet‐printed MHPs for highly efficient and innovative optoelectronic devices is provided. Abstract : Inkjet printing of metal halide perovskites is a promising production technology for many optoelectronic devices. The printing process is highly flexible, digital, mask‐less direct writing technique, and consumes a minimum amount of material during the production process. Aspects such as ink development, substrate modification, and process engineering are of fundamental importance to devise strategies to control the perovskite crystallization.